The effect of a budget-based incentive compensation scheme on job performance: The mediating role of trust-in-supervisor and organizational commitment. Issue 4 (7th November 2016) - Chong, Vincent K.; Law, Maggie B.C.
Abstract : Purpose: This study aims to examine the role of trust-in-supervisor and organizational commitment on the relationship between a budget-based incentive compensation scheme and job performance. Design/methodology/approach: A survey was conducted involving 120 managers from Australian manufacturing firms listed in the Who's Who in Business in Australia electronic database. A partial least squares approach was used to assess the psychometric properties of the theoretical model and proposed hypotheses. Data analysis was conducted using WarpPLS Version 5.0. Findings: The results suggest that the reliance on a high budget-based incentive compensation scheme was found to lead to higher trust-in supervisor, which in turn resulted in higher organizational commitment and improved subordinate job performance. Research limitations/implications: This study is subject to the limitations of survey-based research. Practical implications: This study may assist top management to better understand the importance of designing an effective budget-based incentive compensation scheme to promote high interpersonal trust and organizational commitment among subordinates. Cultivating a climate of trust may help to enhance interpersonal trust between subordinates and their superior, which in turn may lead to higher levels of organizational commitment and improvement in subordinate job performance. Originality/value: This paper elucidates and contributes to the existing literature by suggesting that a budget-based incentive compensation scheme can directly affect subordinates' level of trust in their supervisor, and that trust-in-supervisor can serve as an antecedent to the development and cultivation of subordinates' commitment to the organization, which in turn improves their job performance.